Evaluation of an internet-based animated preparatory video for children undergoing non-sedated MRI - McGlashan, Hannah L.; Dineen, Robert A.; Szeszak, Sofia; Whitehouse, William P.; Chow, Gabriel; Love, Andrew; Langmack, Gill; Wharrad, Heather (British Institute of Radiology, 2018)
Objectives: We evaluate the value of an internet-based educational animated video designed to prepare children for MRI scans, and whether this video reduces scan-related anxiety in children with a neurological disorder, and healthy controls.